Bismuth based perovskite inspired absorbers for optoelectronic applications - Vipinraj Sugathan (Nanyang Technological University, 2022)
Ever increasing population and the dependence on the depleting resources to meet the energy needs is becoming a serious concern worldwide. The dependence on conventional fossil fuels has grave bearings on the environment. Solar energy is hence considered a viable alternative to meet the energy equirements in an environment friendly sustainable manner. Among the various available technologies, the silicon- based solar cells are considered the most promising ones, to potentially serve the energy needs of the entire world. However, the heavy financial constraints involved in production and purification of silicon and the allied implication on environment remains a major concern. Hence, numerous thin film technologies have dominated the research arena for a long time now, with an aim to develop much more sustainable alternatives. The organic-inorganic hybrid halide perovskite with a general structure of ABX3 (where ‘A’ is mostly organic cation, X = halide anion and Pb being the characteristic B site cation), is among the most researched candidates due to their favourable optoelectronic properties. Despite the promises they offer, the halide perovskites are not yet commercialized due to the high ambient instability and toxicity of Pb which is a characteristic component in the same. The stability concerns have been addressed to some extent, but there is a need for extensive research for elimination of lead and making the Perovskites commercially competent. Bismuth-based, lead-free halide double perovskites (LFHDPs) have been considered as a viable less toxic alternative, attracting abundant research attention. Cs2AgBiBr6 being the most explored candidate among them. However, they exhibit wide bandgaps making them potentially less applicable in solar cells. In my research, I employ doping or dilute alloying methods to tune the bandgap of these materials to improve the optoelectronic performances. We introduce a set of novel double perovskite materials, developed by alloying Cs2AgBiBr6, with lead (Pb) and gold (Au) and study the respective properties. Dilute alloying with Pb helped to change the nature of the bandgap from indirect to direct, along with reduction in bandgap, making them promising for solar cell applications. Though the introduction of lead makes it toxic to some extent, its percentage is significantly reduced as compared to the conventional perovskites. This trade-of may be acceptable considering that it helps in improving the optoelectronic properties. Au doping helped to reduce the bandgap to a competitive value, making them potentially applicable as absorbers in solar cells. The emissive properties of the same double perovskite are explored and the role of carrier- lattice interaction and associated self-trapped excitons (STE) on the same is studied. I, develop a better understanding on optoelectronic properties and electron-phonon interaction in Potassium (K+) alloyed Cs2AgBiBr6, while evaluating its potential as a single source tunable light emitter. At low concentrations K+ partially occupying Cs+ site allowing blue-light emissions, while white-light emission occur at higher alloying concentrations of K+. This phenomenon is explained by the Frohlich mechanism. The increased density of STEs and the free exciton (FE) assisted emissions together lead to the PL broadening and white-light emissions. AgBiI4 perovskite inspired materials (PIM) for solar cell application is widely studied, but poor power conversion efficiencies (PCEs) limited their applications in solar cells. These poor performances can be attributed to the poor fill factors due to poor charge transfer. Here I propose the addition of Sn atoms in the precursor solution, that helps in modifying the film morphologies in solution processed thin films, leading to the formation of uniform, and ordered films. Sn is incorporated at the grain boundaries, helping better charge transfer and thus the fill factors improved from 61% to about 75.6%, thus helping to boost the performance of the solar cells. The devices thus developed showed high reproducibility and consistency. The progress of the PIMs is largely limited by the complex and non-uniform morphologies of the thin films. Using the conventional deposition methods, it is difficult to obtain quality films that are free of surface defects and hence the optoelectronic performances of these materials are highly constrained. In my research I introduce a novel two-step modified synthesis method to obtain large area uniform films of Ag3BiI6. Ag and Bi metals are sequentially evaporated and then treated with sublimed iodine vapors in a vacuum chamber. High-quality films with excellent coverage were obtained and applied in perovskite-inspired solar cells. The devices thus fabricated, yielded a power conversion efficiency (PCE) of ~0.7% for large areas, thus, demonstrating the potential to be used in commercial solar cell fabrication. Bismuth sulphoiodide (BiSI) is another material explored for application in for toxicity-free photovoltaics (PV). Its applications in thin-film is however restricted by the lack of methods to obtain pure phases. Here, I design a novel precursor composition to fabricate pure phase BiSI thin-films by simple solution processed spin-coating method. The as-prepared thin-films are characterized by X-ray diffraction studies, optical absorption spectroscopy, X-ray photoelectron spectroscopy, and transmission electron spectroscopy to confirm the phase purity. The films thus developed were p-type and exhibited excellent photoconductivity, presenting their aplicability in PV absorbers. In summary the thesis work emphases on the various limitations in bismuth-based perovskite inspired materials and attempts to improve on the same in order to contribute towards developing commercially viable thin film solar cells.